2018
DOI: 10.20944/preprints201807.0399.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Daily Consumption of a Chocolate Rich in Flavonoids Decreases Cellular Genotoxicity and Improves Biochemical Parameters of Lipid and Glucose Metabolism

Abstract: In recent years, Atherosclerotic Cardiovascular Disease (ACVD), Obesity and Diabetes, have increase exponentially worldwide. In the present work, we evaluate the genoprotective effect of consuming a flavonoids-rich chocolate and the improvement in the biochemical parameters related to the prevention and treatment of cardiovascular risk and metabolic syndrome in young Mexican adults. A randomized, placebo-controlled, double-blind study was undertaken in the Autonomous University of Baja California. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Previous work from our laboratory showed improved serum HDL levels in type 2 diabetic rats treated with hesperidin and naringin [ 21 ]. Long-term consumption of flavonoid-rich foods has been associated with improved circulating levels of total cholesterol, triglycerides, and LDL-cholesterol [ 87 ]. Preclinical in vitro and in vivo studies reported the influence of flavonoids on RCT and HDL function by regulating the activity and expression of hepatic paraoxonase 1 and cholesterol efflux from macrophages [ 46 ].…”
Section: Biological Activities Of Citrus Flavonoidsmentioning
confidence: 99%
“…Previous work from our laboratory showed improved serum HDL levels in type 2 diabetic rats treated with hesperidin and naringin [ 21 ]. Long-term consumption of flavonoid-rich foods has been associated with improved circulating levels of total cholesterol, triglycerides, and LDL-cholesterol [ 87 ]. Preclinical in vitro and in vivo studies reported the influence of flavonoids on RCT and HDL function by regulating the activity and expression of hepatic paraoxonase 1 and cholesterol efflux from macrophages [ 46 ].…”
Section: Biological Activities Of Citrus Flavonoidsmentioning
confidence: 99%
“…Phytochemicals in honey may have suppressing effect on oxidative stress and inflammatory responses [7]. Flavonoids have also shown potential to decrease levels of blood lipids including triglycerides and low-density lipoprotein (LDL)-cholesterol [8]. By inhibition of glucose absorption, increased secretion of insulin, and decreased hepatic gluconeogenesis, polyphenols may also exert an anti-diabetic effect [9].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the lipid profile of these patients, it is possible to resort to NBCs, capable of modulate the lipid metabolism (Table 5). [236,237] PPARs pathways modulation Resveratrol is able to act on lipid metabolism through numerous mechanisms, promoting the reduction in adipogenesis and the increase in lipolysis [241]. Specifically, the main mechanism of the SIRT1 pathway, a nicotinamide dinucleotide (NAD+)-dependent deacetylase, involved in energy and mitochondrial metabolism.…”
Section: Lipid Profilementioning
confidence: 99%
“…In another study, Hamed et al observed an improvement in the lipid profile, in particular a reduction in LDL-C and an increase in HDL-C, in healthy subjects taking 700 mg/day of flavonoids in the form of dark chocolate for one week [ 236 ]. More recently, a randomized and placebo-controlled study conducted by Leyva-Soto et al, revealed that total cholesterol, LDL-C and TG decreased after a daily intake of 2 g of dark chocolate (70%) for 6 months [ 237 ]. The cocoa polyphenols regulate the main pathways involved in both fat synthesis and catabolism.…”
Section: Possible Effects Of Natural Bioactive Compounds In Metabomentioning
confidence: 99%